Proceso de auditoría para determinar el grado de liquidez en una empresa comercial. - Mendez Rivera, Erika Elizabeth (My University, 2018)
The present investigation refers to the audit process with respect to the control of the cash account. The audit to the cash account allows to determine with a degree of security that the transactions carried out are adequate and valid. The control that is exercised in the cash account is of vital importance, because it promotes an appropriate administration of the available resources, as well as determining the operation, whether administrative and financial, of the companies. The objective of this paper is to: Determine the internal audit process through the analysis of the activities carried out by a commercial company with the purpose of achieving an adequate control of the cash account. There are also two specific objectives, these are: 1) Determine the procedures to be executed in the phase of the execution of the audit; 2) Prepare a special exam to the cash account. The research is carried out based on the descriptive and documentary method because a theoretical review of scientific articles, laws, regulations and consultation of accounting policies will be carried out.
La presente investigación se refiere al proceso de auditoría con respecto al control de la cuenta caja. La auditoría a la cuenta caja permite determinar con un grado de seguridad que las transacciones realizadas sean adecuadas y válidas. El control que se ejerce en la cuenta caja es de vital importancia, debido a que promueve una acertada administración de los recursos disponibles, además de determinar el funcionamiento ya sea administrativo y financiero de las empresas. El objetivo del presente trabajo es el de: Determinar el proceso de auditoría interna a través del análisis de las actividades realizadas por una empresa comercial con el propósito de lograr un adecuado control de la cuenta caja. Se plantean además dos objetivos específicos, estos son: 1) Determinar los procedimientos a ejecutarse en la fase de la ejecución de la auditoría; 2) Preparar un examen especial a la cuenta caja. La investigación se realiza a partir del método descriptivo y documental debido a que se llevará a cabo una revisión teórica de artículos científicos, leyes, reglamentos y la consulta a las políticas contables.
Keywords: AUDITORIA; CAJA; EXAMEN ESPECIAL; RAZONABILIDAD; LIQUIDEZ